ANALISIS KETERAMPILAN DASAR LABORATORIUM DENGAN PEMBELAJARAN POGIL PADA MATERI TITRASI ASAM BASA - Rosanti, Widya; Amalia, Nur Rizky; Harjito, Harjito; Susatyo, Eko Budi (Universitas Negeri Semarang, 2019)
The aim of this research was to analyze the basic laboratory skills with environment-based POGIL learning on acid base titration materials. POGIL learning syntax consists of orientation, exploration, concept formation, application, and cover used to train basic laboratory skills. Skills analyzed are prediction skills, observation, measure, communication, and inference. The method used is descriptive qualitative with the results of each value gives an overview of the object under study through the subject data. The result of each basic skill has an average score of 3.66 for predictive skills, 4.11 for observation skill, 4.36 measure skill, 3.83 for communication skill, 3.50 on inference skills of total score 5. Overall this research can be concluded that environment-based POGIL learning on acid-base titration material is effective for training basic laboratory skills for students. There are 30 students got good grades and 2 students got very good grades.